Estudo da atividade antifúngica dos monoterpenos (R)-(+)-citronelal, (S)-(-)-citronelal e 7-hidroxicitronelal sobre o crescimento de Candida albicans isoladas de infecções ungueais - Gouveia, Rawny Galdino (2023)
Onychomycosis is a common disease that affects the nail unit, representing at least 50% of all nail diseases. This chronic nail infection is mainly caused by Candida albicans yeast, responsible for approximately 70% of cases. This condition presents complexity and challenges in treatment. In this study, was investigated the antifungal effect of monoterpenes 7-hydroxycitronellal, (R)-citronellal, and (S)- citronellal, as well as their predictive mechanisms of action on voriconazole-resistant C. albicans onychomycosis. In vitro broth microdilution techniques and molecular docking were applied to predict and complement the mechanisms of action. The main results of this study indicate that C. albicans was resistant to voriconazole but sensitive to (R)-citronellal, (S)-citronellal, and 7-hydroxycitronellal at concentrations of 256, 32, and 64 µg/mL, respectively. Furthermore, there was an increase in the minimum inhibitory concentration (MIC) of the compounds in the presence of sorbitol and ergosterol, indicating that these molecules possibly affect the integrity of the cell wall and membrane of C. albicans. Molecular docking with key proteins involved in fungal cell wall and plasma membrane biosynthesis and maintenance demonstrated the potential for these monoterpenes to interact with two important enzymes: 1,3-βglucan synthase and lanosterol 14α-demethylase. Additionally, the effect of the enantiomers and 7-hydroxycitronellal on inhibiting biofilm formation in Candida albicans strains was investigated. The study found that the compounds inhibited biofilm formation in the tested strains, C. albicans LM 600 and C. albicans ATCC 76645. The enantiomer (R)-citronellal and 7-hydroxycitronellal showed strong antibiofilm activity, while the enantiomer (S)-citronellal exhibited moderate to strong activity. Furthermore, the study evaluated the combination of natural products with antifungal drugs fluconazole and voriconazole, and synergistic effects were observed for both enantiomers in both C. albicans strains, as well as additive and antagonistic effects for the enantiomer (S)-citronellal and indifference for 7- hydroxycitronellal when combined with fluconazole in ATCC 76645 strains. Therefore, the findings of this study indicate that the monoterpenes (R)-citronellal, (S)-citronellal, and 7-hydroxycitronellal are fungicidal against C. albicans in onychomycosis, and these substances likely cause damage to the cell wall and membrane of these microorganisms, possibly by interacting with the enzymes involved in the biosynthesis of these fungal structures. These results provide promising evidence of the antifungal potential of (R)-citronellal, (S)-citronellal, and 7-hydroxycitronellal against C. albicans in cases of onychomycosis.